1987
DOI: 10.1148/radiology.165.3.3685357
|View full text |Cite
|
Sign up to set email alerts
|

Normal brachial plexus: MR imaging.

Abstract: Magnetic resonance (MR) imaging of the brachial plexus was performed in the axial, coronal, and sagittal planes in seven volunteers. Normal structures were delineated by comparison with axial and sagittal cadaver sections and with gross dissection. Differentiation of soft tissues with MR imaging enabled the brachial plexus to be defined from surrounding muscle and vascular structures. Multiplanar imaging demonstrated anatomic detail not previously demonstrated with other radiologic modalities and provided exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(31 citation statements)
references
References 0 publications
0
29
0
2
Order By: Relevance
“…However, diagnosis based on clinical examination alone is often difficult. The contribution of MR imaging to the depiction of those three zones mentioned above has been researched by many investigators [14][15][16][17]. Thoracic outlet can be well visualized in MR imaging with the patient in a comfortable position with the arm alongside the body, but additional postural maneuver, including hyperabduction and external rotation of the arm, is needed in patients with TOS.…”
Section: Brachial Plexusmentioning
confidence: 99%
“…However, diagnosis based on clinical examination alone is often difficult. The contribution of MR imaging to the depiction of those three zones mentioned above has been researched by many investigators [14][15][16][17]. Thoracic outlet can be well visualized in MR imaging with the patient in a comfortable position with the arm alongside the body, but additional postural maneuver, including hyperabduction and external rotation of the arm, is needed in patients with TOS.…”
Section: Brachial Plexusmentioning
confidence: 99%
“…Its multiplanar capability and superior soft tissue contrast allows differentiation of nerve elements from the adjacent tissues [11,12]. CT scan limitations include beam-hardening artifact from bone and metallic clips, restriction to axial planes, ionizing radiation, and the difficulty of differentiating vascular from the other soft tissue structures without the use of intravenous contrast.…”
Section: Discussionmentioning
confidence: 99%
“…CT scan limitations include beam-hardening artifact from bone and metallic clips, restriction to axial planes, ionizing radiation, and the difficulty of differentiating vascular from the other soft tissue structures without the use of intravenous contrast. Armington et al [13] showed that 11 of 30 patients with axillary and supraclavicular lesions were missed due to inadequate visualization of the axillary apex with CT. Coronal and sagittal planes available with MR imaging provide visualization of the entire BP [11]. Although large metastatic tumors involving the BP may be palpable, they often present in "silent" regions such as the axillary apex, the retroclavicular area, the neural foramina, the paravertebral gutter or as an infiltrative process to the adjacent fat and the perineural sheath [13].…”
Section: Discussionmentioning
confidence: 99%
“…Es werden Serien durchgeführt mit den Armen in Neut ralstellung sowie mit den Armen in Hyperabduktion und Außenrotation. Die sa gittale Schichtführung hat sich zur Beurteilung der anatomischen Verhältnisse der oberen Thoraxapertur als besonders geeignet erwiesen (Demondion et al 2000(Demondion et al , 2003Blair et al 1987;Panegyres et al 1993). Das MRProtokoll beinhal tet T1gewichtete Sequenzen der oberen Thoraxapertur (Demondion et al 2003) und eine kontrastmittelverstärkte MRAngiographie (Dymarkowski et al 1999;Hagspiel et al 2000) in koronarer und sagittaler Schichtführung (siehe nachste hende Abbildung).…”
Section: Magnetresonanztomographie (Mrt)unclassified